Scientific production and the development of technology in the production chain of beekeeping (Research, Society and Development, 2021)
The beekeeping agribusiness has stood out for being in full expansion, fulfills the requirements of sustainability, generates income and contributes to a balanced environment. This work seeks to present the evolution of beekeeping in the period from 2000 to 2019 with analysis of the publication of scientific articles and also of the protection scenario through the filing of patent documents for products and processes from the bee chain in the national and international scenario. For this purpose, searches for scientific publications were carried out in the Web of Science database and technology protections in the patent banks of the National Institute of Industrial Property (INPI), European Patent Office (ESPACENET) and in the Latin American Patent Office (LATIPAT). The results allowed to observe a quantity of 21,961 publications of articles and a set of 11,292 deposits of patent documents. China is the largest producer of knowledge according to databases in the period studied. In Brazil, the greatest generator of scientific knowledge related to bee products is the independent depositors, followed by public universities, with publications mostly focused on health. The results obtained in the research demonstrate that beekeeping is a profitable activity, especially in Asian countries that exploit all bee products and have support from the private sector.